Algebra Examples
y=x+1
Step 1
Substitute -2 for x and find the result for y.
y=(-2)+1
Step 2
Step 2.1
Remove parentheses.
y=-2+1
Step 2.2
Remove parentheses.
y=(-2)+1
Step 2.3
Add -2 and 1.
y=-1
y=-1
Step 3
Substitute -1 for x and find the result for y.
y=(-1)+1
Step 4
Step 4.1
Remove parentheses.
y=-1+1
Step 4.2
Remove parentheses.
y=(-1)+1
Step 4.3
Add -1 and 1.
y=0
y=0
Step 5
Substitute 0 for x and find the result for y.
y=(0)+1
Step 6
Step 6.1
Remove parentheses.
y=0+1
Step 6.2
Remove parentheses.
y=(0)+1
Step 6.3
Add 0 and 1.
y=1
y=1
Step 7
Substitute 1 for x and find the result for y.
y=(1)+1
Step 8
Step 8.1
Remove parentheses.
y=1+1
Step 8.2
Remove parentheses.
y=(1)+1
Step 8.3
Add 1 and 1.
y=2
y=2
Step 9
Substitute 2 for x and find the result for y.
y=(2)+1
Step 10
Step 10.1
Remove parentheses.
y=2+1
Step 10.2
Remove parentheses.
y=(2)+1
Step 10.3
Add 2 and 1.
y=3
y=3
Step 11
This is a table of possible values to use when graphing the equation.
xy-2-1-10011223
Step 12